A joint model of location, inventory and third-party logistics provider in supply chain network design. (December 2022) - Wang, Huihui; Fang, Shu-Cherng; Huang, Min; Zhang, Qihuan; Deng, Zhibin
Abstract: Integrated supply chain network design plays an increasingly important role in improving the operational efficiency of a company. This paper studies a novel joint supply chain network model that integrates location, inventory and third-party logistics provider decisions for consideration in a three-level supply chain involving manufacturers, distribution centers (DCs), and retailers. Different from traditional location-inventory problems, the proposed model not only determines the locations of manufacturers and DCs, and how to serve DCs and retailers by manufacturers and DCs, but also chooses potential third-party logistics providers to serve DCs and retailers. The goal is to design an efficient supply chain system to reduce the overall cost including facility cost, inventory cost, and transportation cost to meet the demands of retailers. A nonlinear integer programming model based on multigraph is proposed. To deal with the complex nonlinear terms, we reformulate a mixed-integer nonlinear programming model. Moreover, to deal with the difficulties caused by multigraph, a method based on the generalized Benders decomposition (GBD) is developed. Computational results clearly show the effectiveness of the proposed model and the GBD method. Comparative analysis shows the potential benefits of integrating the third-party logistics provider decisions into the location-inventory model. Highlights: A novel location-inventory model that integrates 3PL providers is presented. A nonlinear integer programming model based on multigraph is proposed. An efficient method based on generalized Benders decomposition has been developed. Some managerial insights show the potential benefits of the integrated model.